Photopyroelectric response of PTCa/PEEK composite - Estevam, Giuliano Pierre [UNESP]; Barros de Melo, Washington Luiz; Sakamoto, Walter Katsumi [UNESP] (American Institute of Physics (AIP), 2011)
A pyroelectric composite made of calcium modified lead titanate ceramic and polyether-ether-ketone high performance polymer was obtained in the film form by hot pressing the ceramic/polymer mixture into the desired composition. After polarization with a suitable electric field, a ceramic composite film (60% vol.) exhibited a pyroelectric figure of merit three times higher than that of a lead zirconate titanate ceramic. The material was used as infrared radiation sensor. The voltage responsivity decreases with the inverse of the frequency showing the same behavior of the thermally thick sensor. The reproducibility of the sensor responses was observed. (C) 2011 American Institute of Physics. [doi:10.1063/1.3552193]